ISLAMIC LAW REVIEW ON INTER-RELIGIOUS MARRIAGES IN INDONESIA BASED ON LEGAL BENEFITS - Notonegoro, Muhammad Hadi; Rinda Listyawati, Peni (Jurnal Hukum Khaira Ummah, 2024)
This study aims to determine and analyze the regulation of interfaith marriage in Indonesia, to determine and analyze that interfaith marriage can be implemented in Indonesia, and to determine and analyze the impact of interfaith marriage in Indonesia. Based on the study, it was concluded that the regulation of interfaith marriage in Indonesia is not regulated by law, but the prohibition of interfaith marriage in Indonesia can be understood in the provisions of Article 2 paragraph (1) of the Marriage Law and Article 10 paragraph (2) of Government Regulation No. 9 of 1975, SEMA Number. 2 of 2023, Article 8 letter f of the Marriage Law Number. 1 of 1974 and Article 44 of the Compilation of Islamic Law (KHI). Interfaith marriage cannot be implemented in Indonesia, because according to Islam, Protestant Christianity, Catholicism, Hinduism, and Buddhism, marriage must be based on government regulations, for Islam it must go through the Religious Affairs Office (KUA) one of the requirements is that it must not be of different religions, then other religions indicate that marriages must be registered at the Civil Registry Office, and must not be of different religions. The impact of interfaith marriages in Indonesia is that if administratively interfaith marriages are considered invalid according to the law and the marriage is not recognized, so that when the registration of the marriage at the civil registry office is rejected, children from interfaith marriages often experience a dilemma in determining their religious beliefs because each parent will put pressure on their children to embrace their own religion.